Molecular variability in Plasmopara halstedii causing downy mildew of sunflower - and RAMESH V. KOTA, SRIKANT KULKARNI*, YASHODA R. HEGDE (Indian Phytopathology, 2007)
Twelve isolates of Plasmopara halstedii collected from different parts of south India were analyzed with RAPD markers. PCR amplification of total genomic DNA with 60 random primers generated unique banding patterns depending upon primers and isolates. Polymorphism per primer ranged from a (OPF19)to 100 per cent with OPF9 primer. The dendrogram of different isolates into groups resulted in one major cluster at 0.85 similarity index comprising of 10 isolates and two isolates formed in a separate cluster.